Reenvisioning Town Meetings as Accessible to Caregivers of Young Children - Arcand, Carolyn (Maine Policy Review, 2025)
This paper presents an analysis of the accessibility of town meeting government to caregivers of babies and young children. The article examines prior research on who typically attends town meetings and explores challenges to caregivers’ attendance. Findings suggest that due to existing challenges, caregivers for young children are less likely to attend town meetings than noncaregivers. The author looks at best practices for inclusive public meetings and generate a model for accessible meeting design with a goal of engaging and supporting caregivers.